Personalized prediction of overall survival in patients with AML in non‐complete remission undergoing allo‐HCT. (16th June 2021) - Hirabayashi, Shigeki; Uozumi, Ryuji; Kondo, Tadakazu; Arai, Yasuyuki; Kawata, Takahito; Uchida, Naoyuki; Marumo, Atsushi; Ikegame, Kazuhiro; Fukuda, Takahiro; Eto, Tetsuya; Tanaka, Masatsugu; Wake, Atsushi; et al.
Abstract: Allogenic hematopoietic stem cell transplantation (allo‐HCT) is the standard treatment for acute myeloid leukemia (AML) in non‐complete remission (non‐CR); however, the prognosis is inconsistent. This study aimed to develop and validate nomograms and a web application to predict the overall survival (OS) of patients with non‐CR AML undergoing allo‐HCT (cord blood transplantation [CBT], bone marrow transplantation [BMT], and peripheral blood stem cell transplantation [PBSCT]). Data from 3052 patients were analyzed to construct and validate the prognostic models. The common significant prognostic factors among patients undergoing allo‐HCT were age, performance status, percentage of peripheral blasts, cytogenetic risk, chemotherapy response, and number of transplantations. The conditioning regimen was a significant prognostic factor only in patients undergoing CBT. Compared with cyclophosphamide/total body irradiation, a conditioning regimen of ≥3 drugs, including fludarabine, with CBT exhibited the lowest hazard ratio for mortality (0.384; 95% CI, 0.266–0.554; p  < 0.0001). A conditioning regimen of ≥3 drugs with CBT also showed the best leukemia‐free survival among all conditioning regimens. Based on the results of the multivariable analysis, we developed prognostic models showing adequate calibration and discrimination (the c‐indices for CBT, BMT, and PBSCT were 0.648, 0.600, and 0.658, respectively). Our prognostic models can help in assessing individual risks and designing future clinical studies. Furthermore, our study indicates the effectiveness of multi‐drug conditioning regimens in patients undergoing CBT. Abstract : Allogenic hematopoietic stem cell transplantation (allo‐HCT) is the standard treatment for acute myeloid leukemia (AML) in non‐complete remission (non‐CR); however, the prognosis is inconsistent. We developed and validated prognostic models (nomograms and web application) to predict the overall survival of patients with non‐CR AML undergoing allo‐HCT (cord blood transplantation, bone marrow transplantation and peripheral blood stem cell transplantation) using a large cohort. The web application is available at https://JSHCT‐AMLWG.shinyapps.io/Predict‐OS‐nonCR‐AML‐post‐HCT/ .